The Use of Crisis Communication Strategies by Erigo in Emergency Management and Plagiarism Issues - Putri, Kinkin Yuliaty Subarsa; Fazli, Luthfi; Wulandari, Helyana; Romli, Nada Arina; Anindhita, Wiratri (Jurnal The Messenger, 2023)
Introduction: Erigo serves as a compelling research subject due to its recent reputation crisis from plagiarism allegations, illustrating how companies can face significant brand challenges. Its application of Image Repair Theory offers insights into effective crisis communication strategies, while the role of social media highlights the dynamics of public perception. Analyzing Erigo’s experience provides valuable lessons for other brands facing similar ethical issues. Methods: This study takes a descriptive qualitative method. Using the case study method. The data source used includes data analysis from several social media platforms, including Instagram and Twitter. In addition, this study draws on data from earlier research. Findings: Erigo used one of Image Repair Theory’s tactics to deal with his reputation crisis: the mortification strategy. Mortification is an approach that involves accepting responsibility for the objectionable action/event, apologizing, and asking for forgiveness. Expressions of remorse are also included in this category. Erigo demonstrated this by apologizing to both the public and the illustrator concerned. Originality: This study becomes novelty because there has been no previous research that discusses how Erigo’s crisis communication strategy deals with this problem. Previous research has also focused more on customer experience and customer brand trust in the Erigo fashion brand.